The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/978-90-481-2530-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Improving UMTS LTE Performance by UEP in High Order Modulation

Abstract: In this contribution we investigate the performance of the UMTS Long Term Evolution (LTE) physical layer using turbo coding and 64QAM with Gray mapping. We show how the mapping of systematic and parity bits to the six different bit positions defining one complex 64QAM symbol influences the convergence of the turbo decoder and thereby the bit error rate (BER) performance as well as number of necessary decoding iterations. Exploiting the unequal error protection (UEP) property of Gray mapped 64QAM results in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…In Reference Lüders et al applied the technique of prioritization QAM constellation mapping, which is achieved by making use of the unequal error protection (UEP) property of the QAM constellation such that an increased protection is provided to the systematic information bits. The authors of Reference have proposed a system combining prioritized constellation mapping, adaptive sign difference ratio (SDR)‐based extrinsic information scaling, and joint source channel decoding (JSCD) in order to enhance the error performance of turbo‐coded 64‐QAM.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference Lüders et al applied the technique of prioritization QAM constellation mapping, which is achieved by making use of the unequal error protection (UEP) property of the QAM constellation such that an increased protection is provided to the systematic information bits. The authors of Reference have proposed a system combining prioritized constellation mapping, adaptive sign difference ratio (SDR)‐based extrinsic information scaling, and joint source channel decoding (JSCD) in order to enhance the error performance of turbo‐coded 64‐QAM.…”
Section: Introductionmentioning
confidence: 99%
“…UEP can be performed on QAM constellations by the bit-reordering scheme proposed in [9]. The authors [9] combined LTE Turbo codes with QAM and then UEP was used to protect the systematic bits more than the parity bits. This provided significant performance gains [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors [9] combined LTE Turbo codes with QAM and then UEP was used to protect the systematic bits more than the parity bits. This provided significant performance gains [9]. In [10], the authors extended the work of [9] with joint source channel decoding for LTE Turbo codes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results showed that the EEP schemes were outperformed by the new proposed UEP scheme. In [5], it was demonstrated that prioritized QAM constellation mapping has a positive impact on the error performance of Turbo Codes by using the UEP characteristics of the QAM constellation where the systematic information bits are given a higher protection. A robust transmission of H.264/AVC coded video using hierarchical QAM (HQAM) was presented in [6].…”
Section: Introductionmentioning
confidence: 99%